2017
DOI: 10.1016/j.neuroscience.2016.10.051
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide inhibits giant depolarizing potentials and abolishes epileptiform activity of neonatal rat hippocampal slices

Abstract: Hydrogen sulfide (HS) is an endogenous gasotransmitter with neuroprotective properties that participates in the regulation of transmitter release and neuronal excitability in various brain structures. The role of HS in the growth and maturation of neural networks however remains unclear. The aim of the present study is to reveal the effects of HS on neuronal spontaneous activity relevant to neuronal maturation in hippocampal slices of neonatal rats. Sodium hydrosulfide (NaHS) (100μM), a classical donor of HS p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 67 publications
(135 reference statements)
1
18
0
Order By: Relevance
“…In addition, H 2 S has been reported to induce a biphasic concentration-dependent effect (32). In the present study, it was observed that NaHS treatment (30 or 100 µmol/kg/day, intraperitoneal administration) manifested neuroprotective effects on TAA-treated mice, consistent with the previous study (33). Therefore, low and increased levels of H 2 S exhibited cytoprotective and cytotoxic effects, respectively (34).…”
Section: Discussionsupporting
confidence: 90%
“…In addition, H 2 S has been reported to induce a biphasic concentration-dependent effect (32). In the present study, it was observed that NaHS treatment (30 or 100 µmol/kg/day, intraperitoneal administration) manifested neuroprotective effects on TAA-treated mice, consistent with the previous study (33). Therefore, low and increased levels of H 2 S exhibited cytoprotective and cytotoxic effects, respectively (34).…”
Section: Discussionsupporting
confidence: 90%
“…The neuro-modulatory role of H 2 S was shown in the central and peripheral nervous system where it promotes the induction of long-term potentiation (LTP) in hippocampus (Abe and Kimura, 1996), inhibits giant depolarizing potentials in neonatal hippocampus (Yakovlev et al, 2017), affects NMDA-mediated currents (Abe and Kimura, 1996; Yakovlev et al, 2017), increases the transmitter release from motor nerve endings (Sitdikova et al, 2011; Gerasimova et al, 2013, 2015), or initiates contractile responses of the rat urinary bladder by stimulation of primary afferent neurons (Patacchini et al, 2004). …”
Section: Introductionmentioning
confidence: 99%
“…In CBS-knockout mice, altering the activity of CBS has been shown to regulate the production of H2S (Eto et al, 2002). In addition, H2S participates in the pathophysiological processes of central nervous system-related diseases, such as epilepsy, stroke, neurodegenerative diseases, and neurotoxicity; its neuroprotective effects have been shown to depend heavily on its concentration and location (Yakovlev et al, 2017). AOAA has been shown to inhibit the expression of CBS, thereby reducing the formation of H2S, inhibiting Ca 2+ influx, and alleviating the intracellular Ca 2+ overload, which alleviates cell damage.…”
Section: Discussionmentioning
confidence: 99%